Principal Policy in Implementing the Project for Strengthening the Profile of Pancasila Students at SDN 032 Tembilahan in Indragiri Hilir - Mona, Marisa; Afrianto, Afrianto; Yuanita, Putri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
The Merdeka Curriculum changes the curriculum structure in schools, starting with driving schools as pioneers who adopt and implement P5. The principal selection process for drive schools involves several stages, highlighting the crucial principals' role in implementing P5. Not all schools will be ready to implement this curriculum, especially non-driving schools. This research aims to describe school principal policies, strategies, influence, and supporting and inhibiting factors in implementing P5 and uses a qualitative approach. Data are obtained through observation, interviews with school principals, teachers, students, and documentation. The research results show that school principals’ policies consist of planning, implementation, and evaluation. Planning involves forming a curriculum acceleration team, preparing KOSP, budgeting, and increasing teacher competency. Implementation involves forming a facilitator team, creating P5 modules, and mentoring. The evaluation highlights the improvements in school readiness, teacher assessment, and P5's orientation towards strengthening character rather than products. The P5 strategy includes understanding, preparing the ecosystem, design, management, processing assessment reports, evaluation, and follow-up. Influential aspects at SDN 032 include competent human resources and strategic location, as supporting factors for P5, while the obstacle is the teacher's slow adaptation to curriculum changes. The research results are expected to contribute to improving the P5 implementation in schools.